New state records and updated checklist of Aphodiini and Eupariini (Coleoptera: Scarabaeidae: Aphodiinae) from Mexico - Minor, Pablo (Zootaxa, 2017)
Thirty one new state records of species of Aphodiinae (Coleoptera: Scarabaeidae) from Mexico are presented, 24 species belong to Aphodiini and seven species to Eupariini into the genera Agrilinellus, Alloblackburneus, Aphotaenius, Ataenius, Blackburneus, Cephalocyclus, Coelotrachelus, Euparia, Euparixia, Geomyphilus, Gonaphodiellus, Gonaphodiopsis, Haroldiellus, Liothorax, Nialaphodius, Odontolytes, Oscarinus, Pharaphodius, and Planolinellus. New records are from the states of Aguascalientes, Baja California, Baja California Sur, Campeche, Colima, Chiapas, Estado de México, Guerrero, Hidalgo, Jalisco, Michoacán, Morelos, Nayarit, Puebla, Sonora, Tabasco, Tamaulipas, Tlaxcala, Veracruz, Zacatecas, and Distrito Federal. A checklist with updated nomenclature is included for the recorded species of Aphodiini and Eupariini from Mexico.